(untitled) (Economic and Political Thought, 2015)
The article focuses on the problems of stimulant, hindrances and regional development measures. A broad theoretical analysis presented in this paper, as stimulants defines pro-development factors through which socio-economic development is possible. On the other hand hindrances are factors that inhibit the development of regions or make it impossible. In a study on the development and competitiveness of regions, regional development measures also play an important role. They are a conglomeration of various indicators (economic, social, environmental) that allow indicate the strengths and weaknesses of the regions, identify opportunities and threats studied areas and allow for conducting comparative analyzes. This article contains research model which is constructed based on the analysis of individual stimulant and hindrances of development and regional development measures which are widespread in the literature, constituting their refresh and extension.